2014
DOI: 10.1021/nl503768r
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Characterization of the Nanoparticle Size Effect on the Mechanical Stability of Nanoparticle-Based Coatings

Abstract: We present an experimental investigation of the mechanical stability of silica nanoparticle-based coatings as a function of the size of the nanoparticles. The coatings are built following a layer-by-layer procedure, alternating positive and negative surface charges. The mechanical stability of the multilayers is studied in water, on the basis of an ultrasonic cavitation test. The resistance of the coating to cavitation is found to remarkably increase with decreasing the size of the nanoparticles, indicating an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 42 publications
(64 reference statements)
0
26
0
Order By: Relevance
“…Hence, establishing stability and cytotoxicity behaviour of such materials/implants are of vital importance. While the use of nanoparticle coatings are prevalent, dissolution of coating ions into the biological environment and loss of functionality over time is possible [ 137 140 ], which has large repercussions involving toxicity to the human body.…”
Section: Stability and Toxicity Of Micro And Nanomaterialsmentioning
confidence: 99%
“…Hence, establishing stability and cytotoxicity behaviour of such materials/implants are of vital importance. While the use of nanoparticle coatings are prevalent, dissolution of coating ions into the biological environment and loss of functionality over time is possible [ 137 140 ], which has large repercussions involving toxicity to the human body.…”
Section: Stability and Toxicity Of Micro And Nanomaterialsmentioning
confidence: 99%
“…We believe it is porosity and strength of the bonding between the grains that affect the mechanical properties of the films. In the case of V s = 0 kV, fragile NP coatings with poor mechanical properties are formed due to the weak adhesive van der Waals interaction between NPs and substrate [ 62 ].When increasing the substrate voltage, the strengthening is attributed to the high temperatures that arise locally when the NPs impact on the substrate [ 63 ]. Due to the high temperatures lead to partial coalescence of the NPs and neck formation.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the “quantum size effect”, the properties of NPs can be greatly influenced by their size . It has been reported that their surface free energy will be enhanced when their size is minimized . When NPs are smaller than 2 nm in diameter, a high surface free energy will keep the NPs in a “boiling state”, which further causes poor stability and thus a tendency to aggregate and loss of catalytic performance…”
Section: Introductionmentioning
confidence: 99%
“…[3] It has been reported that their surface free energy will be enhanced when their size is minimized. [4] When NPs are smaller than 2nmindiameter,ahigh surface free energy will keep the NPs in a" boiling state", which further causes poor stability and thus atendency to aggregate and loss of catalytic performance. [5] Loading of nanomaterials on high-surface-area supports to give heterogeneous catalysts is af easible strategy to improve stability and catalytic performance.…”
Section: Introductionmentioning
confidence: 99%